Transformasi Kawasan Bandara Internasional Lombok Berdasarkan Kajian Spasial-Temporal Menggunakan Google Earth Pro - Asri, Riyadul; Adi Wibowo (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
The phenomenon of urbanization and the construction of Lombok International Airport since 2011 has driven land conversion that has triggered environmental degradation in the surrounding area. The purpose of this study was to identify changes in land use using Google Earth Pro spatially-temporally around the Lombok International Airport area using Post-Classification Comparison method. The research method used is data analysis based on secondary data using image recording from the Google Earth Pro platform in 2013, 2018 and 2022. Spatial processing and analysis using ArcMap 10.8 by carrying out the Visual on Screen Digitization stage. The results of this study indicate that around the Lombok International Airport area there has been a change in land use due to the construction of Lombok International Airport which began in 2011. Fluctuating changes in 2013, 2018 and 2022 occurred at the research location with built-up land variables of 832.355 ha, unbuilt land of 5,339,792 ha, vegetation of 354.763 ha and roads of 0.1556 ha. The results of the Post-Classification Comparison in the research year used with land use and cover on the type of built-up land of 0.638358 ha, unbuilt land 5.339792 ha, roads 0.1546 ha and vegetation of 0.228039 ha. With the area of ​​unbuilt land that is still dominant, policy makers are expected to maintain the condition of the landscape for the sustainability of the ecosystem, human livelihoods, and disaster mitigation.